TAX COLLECTION ON LAND FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Sari, Rasidah Novita; Amri, Faisal (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2023)
Tax is one of the sources for the State which is collected from the people who are coercive to finance the needs of a country. In the view of Islamic economics, taxes are collected as additional income in the event of a vacancy or shortage of the Baitul Mal (State Treasury). In this study, the object of tax is land ownership or those who can use it, referring to Article 4 of Law Number 12 of 1985 and Law Number 12 of 1994 concerning PBB. Subjects who have to pay Land and Building Tax are people or entities/organizations that have rights or benefit from land or buildings. income from land, namely leasing which is included in the final PPh object as stated in Law no. 36 of 2008 in article 4 paragraph (2) letter d namely Leasing of Land and/or Buildings. From this study shows that the collection of taxes on land in Islamic economics is called kharaj. Kharaj is a land tax collected from non-Muslims.